Adverse Events and Factors Associated with Potentially Avoidable Use of General Anesthesia in Cesarean Deliveries - Guglielminotti, Jean; Landau, Ruth; Li, Guohua (Anesthesiology (Philadelphia), 2019)
Compared with neuraxial anesthesia, general anesthesia for cesarean delivery is associated with increased risk of maternal adverse events. Reducing avoidable general anesthetics for cesarean delivery may improve safety of obstetric anesthesia care. This study examined adverse events, trends, and factors associated with potentially avoidable general anesthetics for cesarean delivery. This retrospective study analyzed cesarean delivery cases without a recorded indication for general anesthesia or contraindication to neuraxial anesthesia in New York State hospitals, 2003 to 2014. Adverse events included anesthesia complications (systemic, neuraxial-related, and drug-related), surgical site infection, venous thromboembolism, and the composite of death or cardiac arrest. Anesthesia complications were defined as severe if associated with death, organ failure, or prolonged hospital stay. During the study period, 466,014 cesarean deliveries without a recorded indication for general anesthesia or contraindication to neuraxial anesthesia were analyzed; 26,431 were completed with general anesthesia (5.7%). The proportion of avoidable general anesthetics decreased from 5.6% in 2003 to 2004 to 4.8% in 2013 to 2014 (14% reduction; P < 0.001). Avoidable general anesthetics were associated with significantly increased risk of anesthesia complications (adjusted odds ratio, 1.6; 95% CI, 1.4 to 1.9), severe complications (adjusted odds ratio, 2.9; 95% CI, 1.6 to 5.2), surgical site infection (adjusted odds ratio, 1.7; 95% CI, 1.5 to 2.1), and venous thromboembolism (adjusted odds ratio, 1.9; 95% CI, 1.3 to 3.0), but not of death or cardiac arrest. Labor neuraxial analgesia rate was one of the most actionable hospital-level factors associated with avoidable general anesthetics. Relative to hospitals with a rate greater than or equal to 75%, the adjusted odds ratio of avoidable general anesthetics increased to 1.3 (95% CI, 1.2 to 1.4), 1.6 (95% CI, 1.5 to 1.7), and 3.2 (95% CI, 3.0 to 3.5) as the rate decreased to 50 to 74.9%, 25 to 49.9%, and less than 25%, respectively. Compared with neuraxial anesthesia, avoidable general anesthetics are associated with increased risk of adverse maternal outcomes.